2014
DOI: 10.1016/j.rppneu.2013.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Promoter hypermethylation of DNA repair genes MLH1 and MSH2 in adenocarcinomas and squamous cell carcinomas of the lung

Abstract: Five years survival of lung cancer is 16%, significantly lower than in prostate (99.9%), breast (88.5%) and colon (64.1%) carcinomas. When diagnosed in the surgical stage it increases to 50% but this group only comprises 14-16% of the cases. DNA methylation has emerged as a potential cancer-specific biomarker. Hypermethylation of CpG islands located in the promoter regions of tumour suppressor genes is now firmly established as an important mechanism for gene inactivation. This retrospective study included 40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 16 publications
(14 reference statements)
0
14
0
Order By: Relevance
“…DNA methylation typically occurs at the 5′-position of the cytosine ring within cytosine-phosphate-guanine (CpG) dinucleotides, and DNA methyltransferases (DNMTs) catalyze this reaction [3, 4]. In normal cells, CpG islands of tumor suppressors are usually unmethylated; however, hypermethylation of CpG promoters occurs frequently in tumors [5, 6]. DNA demethylation has the potential to reverse promoter hypermethylation in tumor cells and lead to the reexpression of aberrantly silenced genes, such as tumor suppressor genes (TSGs) of p16 and p15 [7] and cancer testis antigens (CTA) of MAGEA-1 and MAGEA-3 [8], and to induce the sensitivity of tumor cell to anticancer agents.…”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation typically occurs at the 5′-position of the cytosine ring within cytosine-phosphate-guanine (CpG) dinucleotides, and DNA methyltransferases (DNMTs) catalyze this reaction [3, 4]. In normal cells, CpG islands of tumor suppressors are usually unmethylated; however, hypermethylation of CpG promoters occurs frequently in tumors [5, 6]. DNA demethylation has the potential to reverse promoter hypermethylation in tumor cells and lead to the reexpression of aberrantly silenced genes, such as tumor suppressor genes (TSGs) of p16 and p15 [7] and cancer testis antigens (CTA) of MAGEA-1 and MAGEA-3 [8], and to induce the sensitivity of tumor cell to anticancer agents.…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant DNA methylation of gene promoters has previously been observed in various lung cancers (10, 1315, 47, 48). Maintenance of methylation patterns is controlled by DNA methyltransferases (DNMT1, DNMT3), in response to various insults and environmental exposures (1, 6, 49).…”
Section: Discussionmentioning
confidence: 87%
“…Walter et al have demonstrated that members of the DNA‐repair pathway, such as MLH1 , were correlated significantly with lung tumors classification in German. Gomes et al found MLH1 methylation pattern seemed to vary substantially by histological type, with a higher methylation in SCC in Portuguese. However, Geng et al found no significant differences in MLH1 methylation between AC and SCC in Chinese population.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, several studies reported aberrant MLH1 promoter hypermethylation in NSCLC patients . However, using MLH1 methylation in the diagnosis for NSCLC was still debatable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation